Kecerahan Emulsi dan Waktu Pelelehan Gelato yang ditambahkan Stabilizer dari Ekstrak Kulit Pisang Kaya Polifenol - Jatu Megantari; Anang Mohamad Legowo; Ahmad Ni'matullah Al-Baarri (Jurnal Teknologi Pangan, 2022)
Penelitian ini bertujuan untuk mengetahui kecerahan emulsi dan waktu pelelehan gelato yang ditambahkan stabilizer ekstrak kulit pisang kaya polifenol. Materi yang digunakan adalah kulit buah pisang raja nangka (dai UMKM di Kelurahan Kandri, Kabupaten Gunungpati, Semarang), susu sapi, gula, whipping cream, susu skim, kuning telur, lesitin, minyak sayur, etanol 96%, dan aquadest. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan 4 perlakuan penambahan stabilizer ekstrak polifenol (0%; 0,2% ekstrak polifenol; 0,2% CMC; 0,1% CMC + 0,1% ekstrak polifenol ) dan 5 kali pengulangan. Dalam mendapatkan ekstrak polifenol kulit pisang raja nangka menggunakan metode ultrasonik dengan pelarut etanol pada lama waktu ekstralsi 45 menit. Analisis data yang digunakan yaitu Analisis of Varian (ANOVA) pada taraf signifikansi 5%. Berdasarkan anlisis data menunjukkan bahwa penambahan stabilizer dari ekstrak kulit pisang raja nangka kaya polifenol memberi pengaruh nyata (p<0,05) terhadap kecerahan emulsi dan waktu pelelehan gelato. Hasil uji kecerahan emulsi dengan penambahan ekstrak polifenol perlakuan  0%; 0,2% ekstrak polifenol; 0,2% CMC; 0,1% CMC + 0,1% ekstrak polifenol secara berurutan (72,48 ± 1,27c; 68,10 ± 1,49a; 77,55 ± 0,85d; 70,37 ± 0,61b). Hasil uji waktu pelelehan gelato perlakuan  0%; 0,2% ekstrak polifenol; 0,2% CMC; 0,1% CMC + 0,1% secara berurutan  yaitu  (16,25±0,08a ;18,25±1,00bc ; 17,12±0,33ab; 19,42±2,20c). The aim of this study was to determine the brightness of the emulsion and the melting time of gelato with the addition of polyphenol-rich banana peel extract stabilizer. The materials used were banana jackfruit peel (from SMEs in Kandri Village, Gunungpati Regency, Semarang), cow's milk, sugar, whipping cream, skim milk, egg yolk, lecithin, vegetable oil, 96% ethanol, and aquadest. The experimental design used was a completely randomized design (CRD) with 4 treatments adding stabilizer polyphenol extract (0%; 0.2% polyphenol extract; 0.2% CMC; 0.1% CMC + 0.1% polyphenol extract) and 5 repetition times. In obtaining polyphenolic extracts of Raja jackfruit peel using ultrasonic method with ethanol solvent at extraction time of 45 minutes. Analysis of the data used is the Analysis of Variance (ANOVA) at a significance level of 5%. Based on data analysis, it was shown that the addition of stabilizer from banana peel extract rich in polyphenols had a significant effect (p<0.05) on the emulsion brightness and gelato melting time. The results of the brightness test of the emulsion with the addition of 0% polyphenol extract; 0.2% polyphenol extract; 0.2% CMC; 0.1% CMC + 0.1% polyphenol extract respectively (72.48 ± 1.27c; 68.10 ± 1.49a; 77.55 ± 0.85d; 70.37 ± 0.61b). The results of the gelato melting time test were 0%; 0.2% polyphenol extract; 0.2% CMC; 0.1% CMC + 0.1% respectively (16.25±0.08a ;18.25±1.00bc; 17.12±0.33ab; 19.42±2.20c). The aim of this study was to determine the brightness of the emulsion and the melting time of gelato with the addition of polyphenol-rich banana peel extract stabilizer. The materials used were banana jackfruit peel (from SMEs in Kandri Village, Gunungpati Regency, Semarang), cow's milk, sugar, whipping cream, skim milk, egg yolk, lecithin, vegetable oil, 96% ethanol, and aquadest. The experimental design used was a completely randomized design (CRD) with 4 treatments adding stabilizer polyphenol extract (0%; 0.2% polyphenol extract; 0.2% CMC; 0.1% CMC + 0.1% polyphenol extract) and 5 repetition times. In obtaining polyphenolic extracts of Raja jackfruit peel using ultrasonic method with ethanol solvent at extraction time of 45 minutes. Analysis of the data used is the Analysis of Variance (ANOVA) at a significance level of 5%. Based on data analysis, it was shown that the addition of stabilizer from banana peel extract rich in polyphenols had a significant effect (p<0.05) on the emulsion brightness and gelato melting time. The results of the brightness test of the emulsion with the addition of 0% polyphenol extract; 0.2% polyphenol extract; 0.2% CMC; 0.1% CMC + 0.1% polyphenol extract respectively (72.48 ± 1.27c; 68.10 ± 1.49a; 77.55 ± 0.85d; 70.37 ± 0.61b). The results of the gelato melting time test were 0%; 0.2% polyphenol extract; 0.2% CMC; 0.1% CMC + 0.1% respectively (16.25±0.08a ;18.25±1.00bc; 17.12±0.33ab; 19.42±2.20c).